The Fauré song cycles : poetry and music, 1861-1921 - Rumph, Stephen C. (University of California Press, 2020)
"Gabriel Fauré's mélodies offer an inexhaustible variety of style and expression that has made them the foundation of the French art song repertoire. During the second half of his long career, Fauré composed all but a handful of his songs within six carefully integrated cycles. Far more than Debussy, Ravel, or Poulenc, he crafted his song cycles as integrated works, reordering poems freely and using narratives, key schemes, and even leitmotifs to unify the individual songs. This book explores the peculiar vision behind each synthesis of music and verse, revealing the astonishing imagination and insight of Fauré's musical readings"--